2000
DOI: 10.1002/(sici)1099-1573(200002)14:1<54::aid-ptr540>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone 5?-reductase inhibitor bisnaphthoquinone derivative fromImpatiens balsamina

Abstract: The 35% EtOH extract of aerial parts of Impatiens balsamina L. has been investigated for activity against testosterone 5α‐reductase. Activity‐guided fractionation led to the identification of the bisnaphthquione derivative named impatienol (1), 3‐hydroxy‐2‐{[3‐hydroxy‐1,4‐dioxo (2‐naphthyl)] ethyl} naphthalene‐1,4‐dione, which exhibited significant testosterone 5α‐reductase inhibitory activity. This 5α‐reductase inhibitory compound has been previously synthesized, but this is the first report of its isolation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…1,4-naphthoquinone was extracted from a natural source for the first time by Ishiguro et al that showed the significant testosterone 5AR inhibitory activity (57). Al-though Ishiguro et al examined the inhibitory activity of 1,4-naphthoquinone, the current study findings showed that it has the lowest binding energy (-7.1 kcal/mol), compared to other inhibitors.…”
Section: Discussionmentioning
confidence: 62%
“…1,4-naphthoquinone was extracted from a natural source for the first time by Ishiguro et al that showed the significant testosterone 5AR inhibitory activity (57). Al-though Ishiguro et al examined the inhibitory activity of 1,4-naphthoquinone, the current study findings showed that it has the lowest binding energy (-7.1 kcal/mol), compared to other inhibitors.…”
Section: Discussionmentioning
confidence: 62%
“…Especially 4-azasteroids such as finasteride and dutasteride have been developed for clinical purposes [4], [5]. Naturally occurring non-steroidal inhibitors of 5a-reducatse have been reported, for example, (±)-epigallocatechin 3-gallate [6], chlorophorin [7], bisnaphthoquinone derivatives [8], ostenol [9] and a-linolenic acid [10].…”
mentioning
confidence: 99%